Nanomaterials in fire protection: Innovations for enhanced safety and durability - N.B. Singh (3218844) (2025)
Fire hazards continue to pose serious threats to human life, infrastructure, and the environment, thereby demanding the development of advanced and effective fire protection strategies. In recent years, nanomaterials have emerged as a promising frontier in flame retardancy, owing to their superior thermal stability, high surface area, and multifunctional properties. This review provides a comprehensive overview of the application of nanomaterials—such as nanoparticles, nanotubes, nanosheets, and nanocomposites, in improving fire resistance across various sectors, including construction, electronics, textiles, and transportation. The mechanisms through which nanomaterials enhance flame retardancy include forming thermal barriers, promoting catalytic charring, and suppressing smoke and toxic gases. Nanomaterials offer enhanced efficiency, long-term durability, and reduced environmental impact compared to traditional flame retardants. Furthermore, integrating nanotechnology with smart sensors and adopting green synthesis techniques presents innovative pathways for developing sustainable and intelligent fire protection systems. Despite these advantages, challenges such as production scalability, cost-effectiveness, and regulatory compliance remain significant hurdles. Nevertheless, ongoing research and technological advancements are addressing these issues, pushing the field forward. This review critically discusses the current state of research, key benefits, existing challenges, and prospects of nanomaterials in fire protection, emphasizing their transformative potential in enhancing safety across multiple modern industries. Other Information Published in: Nano-Structures & Nano-Objects License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.nanoso.2025.101497